RET gene rearrangements occur in a subset of pancreatic acinar cell carcinomas - Chou, Angela; Brown, Ian S.; Kumarasinghe, M. Priyanthi; Perren, Aurel; Riley, Denise; Kim, Yoomee; Pajic, Marina; Steinmann, Angela; Rathi, Vivek; Jamieson, Nigel B.; Verheij, Joanne; van Roessel, Stijn; et al. (Modern pathology, 2020)
Pancreatic acinar cell carcinoma is relatively rare (1 to 2% of pancreatic malignancies) but may be under-recognized. In contrast to pancreatic ductal adenocarcinoma, most acinar cell carcinomas lack mutations in KRAS , DPC , CDKN2A or TP53 , but appear to have a high incidence of gene rearrangements, with up to 20% reported to be driven by BRAF fusions. With the development of a new class of RET-specific tyrosine kinase inhibitors, which appear to have particularly strong activity against RET gene rearranged tumours, there is now considerable interest in identifying RET gene rearrangements across a wide range of cancers. RET rearrangements have been reported to occur at a very low incidence (<1%) in all pancreatic carcinomas. We postulated that given its unique molecular profile, RET gene rearrangements may be common in acinar cell carcinomas. We performed fluorescent in-situ hybridization (FISH) studies on a cohort of 40 acinar cell spectrum tumours comprising 36 pure acinar cell carcinomas, three pancreatoblastomas and one mixed acinar-pancreatic neuroendocrine tumour. RET gene rearrangements were identified in 3 (7.5%) cases and BRAF gene rearrangements in 5 (12.5%). All gene rearranged tumours were pure acinar cell carcinomas. Our findings indicate that amongst all pancreatic carcinomas, acinar carcinomas are highly enriched for potentially actionable gene rearrangements in RET or BRAF . FISH testing is inexpensive and readily available in the routine clinical setting and may have a role in the assessment of all acinar cell carcinomas—at this stage to recruit patients for clinical trials of new targeted therapies, but perhaps in the near future as part of routine care.